Development of an inducible pol III transcription system essentially requiring a mutated form of the TATA-binding protein - Meissner, Wolfgang (Oxford University Press, 2001)
We attempted to devise a transcription system in which a particular DNA sequence of interest could be inducibly expressed under the control of a modified polymerase III (pol III) promoter. Its activation requires a mutated transcription factor not contained endogenously in human cells. We constructed such a promoter by fusing elements of the β-lactamase gene of Escherichia coli, containing a modified TATA-box and a pol III terminator, to the initiation region of the human U6 gene. This construct functionally resembles a 5′-regulated pol III gene and its transcribed segment can be exchanged for an arbitrary sequence. Its transcription in vitro by pol III requires the same factors as the U6 gene with the major exception that the modified TATA-box of this construct only interacts with a TATA-binding protein (TBP) mutant (TBP-DR2) but not with TBP wild-type (TBPwt). Its transcription therefore requires TBP-DR2 exclusively instead of TBPwt. In order to render the system inducible, we fused the gene coding for TBP-DR2 to a tetracycline control element and stably transfected this new construct into HeLa cells. Induction of such a stable and viable clone with tetracycline resulted in the expression of functional TBP-DR2. This system may conceptually be used in the future to inducibly express an arbitrary DNA sequence in  vivo under the control of the above mentioned promoter.